2007
DOI: 10.1080/07420520701800686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time‐of‐Day‐Specific Strength Training on Serum Hormone Concentrations and Isometric Strength in Men

Abstract: A time-of-day influence on the neuromuscular response to strength training has been previously reported. However, no scientific study has examined the influence of the time of day when strength training is performed on hormonal adaptations. Therefore, the primary purpose of this study was to examine the effects of time-of-day-specific strength training on resting serum concentrations and diurnal patterns of testosterone (T) and cortisol (CORT) as well as maximum isometric strength of knee extensors. Thirty eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 32 publications
7
75
0
1
Order By: Relevance
“…The literature suggests that the best moments of peak performance are related to body temperature [15] with a worse performance in the morning and a better outcome in the afternoon / evening [16]. In our study we found a 2% increase in body temperature, which leads us to think that this increased tendency to perform better during the night can be directly related to the increase in body temperature, in corroborates with other studies which indicate values larger afternoon / evening [16,17,18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The literature suggests that the best moments of peak performance are related to body temperature [15] with a worse performance in the morning and a better outcome in the afternoon / evening [16]. In our study we found a 2% increase in body temperature, which leads us to think that this increased tendency to perform better during the night can be directly related to the increase in body temperature, in corroborates with other studies which indicate values larger afternoon / evening [16,17,18].…”
Section: Discussionsupporting
confidence: 82%
“…In our study we found a 2% increase in body temperature, which leads us to think that this increased tendency to perform better during the night can be directly related to the increase in body temperature, in corroborates with other studies which indicate values larger afternoon / evening [16,17,18].…”
Section: Discussionsupporting
confidence: 80%
“…Usually, peak performances were found to occur in the early evening and correspond to the maximum body (Aloui et al, 2012;Reilly et al, 2007, Bernard et al, 1998Melhim et al, 1993;Souissi et al, 2010). Although the exact mechanisms explaining this relationship remain unclear, it has been suggested that the increase in body temperature allows an increase in energy metabolism, improved muscle compliance, facilitate actin-myosin crossbridging (Weipeng et al, 2011), enhance metabolic reactions, increase the extensibility of connective tissue, reduce muscle viscosity and increase conduction velocity of action potentials (Sedliak et al, 2007). Even though it is still largely accepted that temperature is the primary circadian indicator of physical performance, recent evidence has challenged the traditional views about the relationship between body temperature and exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, RT itself decreased Akt phosphorylation. The control group results ensured that the results were not due to repeated biopsy, diurnal rhythm, or time of year (47,57).…”
Section: Discussionmentioning
confidence: 99%
“…1). A control group was included, and all the measurements were always carried out at the same time of day to exclude the effects of biopsy sampling or effects of time of year or daily variations (47,57). All the measurements were preceded by at least 2 days of rest from physical activity.…”
Section: Designmentioning
confidence: 99%